Burnout Management Model Based on Job Crafting Approaches for Nurses in Hospitals - Devy Syanindita Roshida; Eska Distia Permatasari; Candra Ferdian Handriyanto; Suci Dwi Cahyani; Anggun Novitria Ramadan (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Workplace burnout is becoming a health concern as well as a problem that affects overall productivity.  The increasing frequency of these incidents highlights the need for all parties involved to carefully analyze them. In the context of this study, early observations revealed that nurses were dealing with rotating shift patterns, extreme workloads, and emotional weariness. These findings demonstrate the urgent need for strategies to increase personal resources and reduce burnout. This study aimed to investigate how a job crafting strategy that considers organizational commitment and leadership style can help nurses manage burnout. Methods: This study used a control group and quasi-experimental design. Organizational commitment and leadership style were independent variables, job crafting was the moderating variable, and burnout was the dependent variable. The intervention was given in several staggered sessions that corresponded with the nurses' rotating shift patterns to ensure complete participation without interfering with patient care. Each variable was measured using validated tools with predetermined scoring systems. Results: The results demonstrated that the levels of burnout among nurses were significantly impacted by both organizational commitment and leadership style. Additionally, job crafting is crucial for preventing or mitigating burnout. Conclusion: This study shows that organizational commitment and leadership style are possible influences on a burnout model among nurses, and that job crafting is a useful strategy. To increase resilience, reduce the risk of burnout, and improve care quality, hospitals are urged to include job crafting training in their continuing professional development programs.